SDG-11 and smart cities: Contradictions and overlaps between social and environmental justice research agendas - Sengupta, Ushnish; Sengupta, Ulysses (Frontiers in Sociology, 2022)
There is an increased role Information and Communications Technology (ICT) plays in the achievement of Sustainable Development Goals (SDGs). This paper focuses specifically on SDG-11 “Make cities and human settlements inclusive, safe, resilient and sustainable” and how cities are increasingly incorporating ICT towards this goal. The public discourse on Smart Cities suggests economic, social and environmental benefits are possible through the use of Information and Communication Technology (ICT). However, the increased deployment and use of digital infrastructure and processes in the name of sustainability and optimization itself is the focus of a growing body of critical literature on Smart Cities. This mini-review collates critical literature on digital infrastructures and processes related to SDG-11 and Smart Cities to identify areas of significance for further research. Although many Smart City projects discuss sustainability benefits, the distribution of benefits and risks across different communities is rarely examined. An increased use of ICT in Smart City projects can provide environmental benefits to some communities, while shifting the burden of risks to other communities. An increased use of ICT has its own energy and resource impacts that has implications for sustainability beyond the geography of individual cities to global impacts. The lifecycle and supply chain impacts of advanced ICT projects are being identified and documented. The end user of the Smart City projects may benefit significantly from the increased use of ICTs, while the environmental costs are often borne by disparate communities.